Best impressions in hospitality : your professional image for excellence - Michael, Angie, 1948- 4 0 16; 5 (Africa Delmar/Thomson Learning, 2000)
Presents a comprehensive guide to a career in the hospitality industry and provides information on appearance, grooming, body language, customer relations, and business etiquette in order to develop the skills necessary to succeed.
Includes bibliographical references (p. [203]-206) and index.
Adult;Adult
Keywords: 2 -- 0; 6; Employees.;Employees.;Employees.;Employees. -- Hotels;Restaurants;Hotels and motels;Restaurants; 20; 2